Virtual vitality: unveiling the attitudes of Malaysian consumers towards online dietary supplement purchases - Hussin, Ruhaya; Ahmad Zulkifli, Nur Ain; Mohd. Abd. Majid, Hayati Adilin; Ahmad Sharoni, Siti Khuzaimah (Persatuan Ekonomi Pengguna dan Keluarga Malaysia, 2023)
The Covid-19 pandemic has significantly changed consumer behavior, with increasing reliance on online platforms for various needs, including the purchase of dietary supplements. This study examines the relationship between Malaysians' attitudes towards online purchase of dietary supplements, perceived usefulness, perceived ease of use, impulse buying and social media marketing. A purposive sample of one hundred Malaysian participants aged 20 to 45 years who currently purchase dietary supplements online and use them daily completed an online survey. The data was analyzed using Pearson product-moment correlation. Results show that perceived usefulness (r = .34, p <.001), perceived ease of use (r = .50, p <.001), and social media marketing (r = .24, p <.010) are positively correlated with consumers' attitudes towards buying supplements online. These results suggest that the more social media marketing was used to promote supplements, the higher the perceived usefulness and ease of use of the online platforms, and the more positive consumers were towards purchasing supplements online. This sheds light on the evolving dynamics of online dietary supplement purchasing behavior among Malaysian consumers during Covid-19. These findings are valuable for companies and marketers looking to improve their strategies and effectively target the Malaysian market in line with government regulations and guidelines.